«Шестоднев» Василия Кесарийского и притчи Мхитара Гоша - Вардазарян, Ольга
The Hexaemeron of Basil of Caesarea exerted a serious literary influence on Mkhit‘ar Gosh (1130–1213), of whose 190 parables at least twelve are, in one way or another derived from this work. Gosh borrows from the Hexaemeron, on several different levels, sometimes combining its contents with other sources, sometimes adapting an entire plot (with the same passage occasionally serving as the basis for several parables) or simply making use of some particular detail. Mkhit‘ar parables are often composed on the basis of a certain conflict discovered in the narrative of his source material; at the same time, as a rule, he composes the exhortation or “moral” of the parable independently, although sometimes he repeats it in general outlines after Basil. The comparison of the Mkhit‘ar’s parables with their sources allows us to observe the medieval Armenian rhetor at work, preparing exercise material for his students, or comprehensible and entertaining edification for his flock. Բարսեղ Կեսարացու «Յաղագս վեցօրեայ արարչութեան» երկը լուրջ ազդեցություն է ունեցել Մխիթար Գոշի վրա. 190-ից առնվազն տասներկու առակ այս կամ այն կերպ բխում է այս աշխատությունից: Գոշն իր առակների համար փոխառել է Վեցօրեայքից, երբեմն այն զուգակցելով այլ աղբյուրների հետ, կա՛մ ամբողջական սյուժեներ (նույն տեղին կարող է հիմք ծառայել մի քանի առակի համար), կա՛մ սյուժեի համար որևէ կարևոր մանրամաս։ Մխիթարը առակներ է գրում՝ իր աղբյուրի պատմության մեջ որոշակի բախում նկատելով։ Միևնույն ժամանակ նա առակի հորդորը, որպես կանոն, ինքնուրույն է կառուցում, թեև երբեմն ընդհանուր գծերով կրկնում է Բարսեղինը։ Առակների համեմատությունը սկզբնաղբյուրների հետ թույլ է տալիս դիտարկել միջնադարյան հայ ճարտասանի աշխատանքը, որն իր աշակերտների համար վարժությունների նյութ կամ իր հոտի համար՝ հասկանալի ու հետաքրքրական խրատ է պատրաստում:
Keywords: Филология